Industry Chain and Technology Trends in China's Solid-state Battery Industry. Issue 1 (June 2021) - Zhang, Lei; Liu, Yingqi; Pang, Beibei
Abstract: Solid-state battery is different from traditional lithium-ion battery, which is a kind of battery using solid electrode and solid electrolyte, and it has the advantages of high safety, long life, high charging and discharging efficiency, good high temperature resistance, simple assembly and processing, and easy to scale up. This paper first analyzes the industrial chain of solid-state batteries in China and the stakeholders in the process of industrial development, and finally draws a technology roadmap for the development of China's solid-state battery industry based on industrial characteristics. In the future, along with energy transformation and national policy support, the focus should be on solid state electrolytes for solid state batteries, and gradually realize the development path of solid state battery electrolytes from liquid state of traditional lithium-ion batteries to solid-liquid hybrid, gel, solid state, and all-solid state.